THE OVERCOMING OF ILLEGAL LOGGING IN CENTRAL SULAWESI - Salam, Johnny (Tadulako University, 2016)
Abstract This study aimed to understand the effectiveness of crime prevention and illegal logging in Central Sulawesi , and factors - factors affecting the crime prevention efforts of illegal logging in the area is , as well as how participation and cultural ' differences community crime prevention efforts against illegal logging in Central Sulawesi . The singer research approach using socio- legal research methods . Results Singer discovered Implementation crime prevention of illegal logging in the region of Central Sulawesi province , as far as Singer Not Operate Effectively Walk ; As well as optimal NOT illegal logging crime prevention efforts in the region of Central Sulawesi province , at least influenced by three factors ; ( 1 ) low capacity of Human Resources , ( 2 ) There has been used to support the inadequacy of the law enforcement process . ( 3 ) the low level of awareness of the law society. Alpha Keywords: Overcoming,Â Illegal Loggin, Central Sulawesi